G121(P) The new (2016) junior doctors contract: experiences of yorkshire-based paediatrics trainees. (12th March 2018) - Payne, F; Redman, M
Abstract : Aims: This project aims to explore the experiences of Yorkshire-based paediatrics trainees of all grades following the recent transition of some trainees to the new (2016) terms and conditions of service (TCS) 1 for junior doctors in England. The authors intend to identify areas which can be addressed to improve the experience of paediatrics trainees in Yorkshire. Methods: An electronic survey was designed and circulated to paediatric trainees of all grades in the Yorkshire School of Paediatrics between 17th–31 st July 2017. Results: Ninety (25%) out of 361 trainees responded (including those on maternity leave, excluding those out of programme). Sixty-six respondents (73%) were full time trainees. The respondents were equally split between those on the 2016 TCS and those on the old (2002) TCS. Thirteen (30%) of those on the new TCS had exception reported, with five of the 13 trainees (38%) having experienced exception reports being actioned within two weeks, and two respondents (5%) having experienced a work schedule review. Nineteen (44%) of respondents were either dissatisfied or very dissatisfied with the new contractual limits on working hours. The main positive experiences identified were: rest rostering, pay, exception reporting, awareness of rest entitlements. The main negative experiences identified were: swapping shifts more difficult due to safe working hours limits, rota gaps, pay disparity, lower morale. Conclusion: Work is ongoing to begin to address some of these issues in Yorkshire. The results highlighted both contractual and extra-contractual issues. More work is needed to address concerns identified by paediatrics trainees, particularly around morale and rota gaps. Trainees should be encouraged to exception report and exception reports should be actioned within the appropriate timeline. Further work can be pursued to explore if these results are comparable across England, and across other specialty training programmes. Reference: . Junior Doctors Termsand Conditions of Service. NHS Employers . http://www.nhsemployers.org/case-studies-and-resources/2016/05/junior-doctors-terms-and-conditions-of-service [Accessed: 14/10/17].